1977
DOI: 10.1080/15287397709529530
|View full text |Cite
|
Sign up to set email alerts
|

Sites in nucleic acids reacting with alkylating agents of differing carcinogenicity or mutagenicity

Abstract: The site of alkylation of a nucleic acid, in vivo, is greatly dependent on the type of alkylating agent. Most alkylating agents of low mutagenicity or carcinogenicity (such as dimethylsulfate) react primarily with the ring nitrogens. The carcinogenic N-nitroso compounds have a great affinity for alkylating oxygens and react with all ring oxygens as well as the phosphodiesters and, in the case of RNA, with the 2'-O of ribose. Ethylating agents, though in absolute terms less reactive than the corresponding methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…Singer and coworkers have demonstrated in recent years that the highly carcinogenic alkyl nitroso compounds preferentially alkylate the oxygens when acting on nucleic acids (8)(9)(10)(11)(12). One objective of current research is to ascertain the biological consequences of specific modifications of this type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singer and coworkers have demonstrated in recent years that the highly carcinogenic alkyl nitroso compounds preferentially alkylate the oxygens when acting on nucleic acids (8)(9)(10)(11)(12). One objective of current research is to ascertain the biological consequences of specific modifications of this type.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have found that the highly carcinogenic N-nitroso alkylating agents not only favor the alkylation of the 06 of G, but also react to a high extent with all three pyrimidine oxygens (02 and 04 of U or T, 02 of C) as well as the -0 of the phosphodiesters and, in RNA, the 02' of ribose (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Alkylation of oxygen atoms of purines and pyrimidines of DNA has been suggested to be critical to mutagenesis and carcinogenesis (40) and a positive correlation has been found between tumorigenesis and the formation and persistence of the promutagenic lesion 06 alkylguanine in target tissues (12,(23)(24)(25)31,33 Ci/mmole) were supplied by New England Nuclear Corporation, (Boston, MA). Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…It (24). O-Alkylated pyrimidines, such as O2_ and 04-thymine, occur in greater proportion relative to 06-alkylguanine following exposure to ethylating agents (27). Since the 0-alkylpyrimidines are removed from liver DNA more slowly (28,29)…”
Section: Introductionmentioning
confidence: 99%
“…Cell specificity in carcinogenesis due to alkylating agents will depend on the ability of different cell populations to activate the carcinogen, their mitogenic response, their capacity to remove promutagenic DNA lesions and the nature of the alkylating agent. For instance, the major promutagenic lesion produced by SN1 methylating agents is O6MG (27). It (24).…”
Section: Introductionmentioning
confidence: 99%